A Brief Review of Paradigm Shifts in Prevention of Alzheimer’s Disease: From Cognitive Reserve to Precision Medicine - Hahn, Changtae; Lee, Chang Uk (Frontiers in Psychiatry, 2019)
Alzheimer’s disease (AD) and related dementias can be an enormous economic burden for taxpayers, patients, their families, medical systems and society as a whole. Since disease-modifying treatments have failed, several studies have instead focused on a paradigm shift for preventing and treating Alzheimer’s disease. A higher cognitive reserve (e.g., greater education, occupational attainment, or more leisure activities) is associated with protection against disease-related cognitive decline. Precision medicine aims to optimize the effectiveness of disease prevention and treatment by considering specific biological components of individuals. We suggest that research into cognitive reserve and precision medicine could be a key to overcoming the limitations of traditional approaches to the prevention and treatment of AD.